The prevalence of Helicobacter pylori infection in Baqubah city - Hameed Jameel, Nadia; Shakir Motib, Anfal; Methab Athab, Ahmed (Diyala Journal of Medicine, 2020)
Background: Helicobacter pylori are the most common cause’s peptic ulcer disease, and it is transmitted by oral-oral, fecal-oral and gastric oral. The prevalence of this bacteria depends on age, sex, smoking or non-smoking and also chronic disease such as diabetes. Objective: To determine the infection of H. pylori in Baqubah city and its associated with age and gender of patients. Patients and Methods: H. pylori diagnosed by used rapid urease test and histopathology test. From 200 studied groups, 127 (63.5%) males and 73 (36.5%) females ages ranged from (10 to ≥ 60) years were collected from Baqubah teaching hospitals, during the period from September 2018 till January 2019. From 200 studied groups 110 considered patients after initial diagnosis by endoscopic unit (presence symptoms) and 90 considered control group (absence symptoms). Two types of samples were collected from each studied groups including gastric biopsy specimens for rapid urease test and histopathology test to detect H. pylori infection. Results: The result of this study shows that H. pylori infection was detected by rapid urease test which appears positive results in 86 patients (78.2 %), and the positive results of histopathology test were 10 (9.0%). The incidence of H. pylori infection in male more than in female as the percentage (70.00%) and (30.00%), respectively. Minimum age was 10 years and maximum was ≥ 60. The highest age specific frequency in studied groups is in the age group (40-49) & (50-59) years old. Conclusion: The prevalence rate of gastric ulcer caused by H. pylori in Baqubah city was high and it is detected by rapid urease test which showed more accurate than histopathological test. In addition, the results showed that the rate of incidence in males more than in females, and in (40-49)&(50-59) more than other ages.